Generasi Z dan Dakwah Moderasi Beragama di Media Sosial - Alfia Aulia; Kasja Eki Waluyo; Abdul Azis (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
The purpose of this research is to study the role of Generation Z in spreading religious moderationvalues through social media, and to identify the challenges and opportunities they face in the digital era.Generation Z grows up in an environment closely tied to digital technology advancement, making social media aprimary platform for their religious and social expression. Creating creative visual content, such as memes andshort videos, is a relevant form of expression used to preach and effectively spread messages of tolerance. Adescriptive qualitative method based on literature study was used comprehensively in this research. Variousscientific literatures and previous journal articles served as the main data sources. The study shows that althoughsocial media offers broad opportunities for attractive and inclusive moderate preaching, there are still majorchallenges. These include the massive spread of hoaxes, disinformation, increased polarization in the virtualpublic space, and the real threat of digital extremism. Therefore, improving digital literacy combined withcomprehensive religious literacy is crucial. This aims to shape Generation Z to think critically, act wisely infiltering information, and ultimately become active agents of peace both in the real world and in the digitalecosystem.